ELECTROLYSIS OF COPPER FORM STRIPPING SOLUTIONS FOR ETCHING PRINTED CIRCUIT BOARDS - Kondratieva E.S.; Gubin A.F.; Brodsky V.A.; Kolesnikov V.A.; Zhurinov M.; Bayeshov A.B.; Brodskiy A.R. (Academic Scientific Journal of Chemistry, 2019)
The article reviews the liquid extraction - electrolysis based etching solution regeneration process for printed circuit boards. It describes process conditions providing the electrolysis of copper from sulphate solutions that are formed at the stage of stripping (re-extraction) of copper ions (II) from organic extractants. Tests have been carried out in an industrial environment. It shows that the electrolysis of copper proceeds generating high current efficiency where a stripping solution contains 1.0 mol/l of sulfuric acid and 0.8 - 1.0 mol/l of copper ions (II), the current density is 1.0 - 6.0 A/ dm2 and electrolyte is mixing. An analysis has been made of the composition of cathode copper obtained as a result of electrolysis from the reference electrolyte and stripping solutions upon contact with organic extractants. It has been found that the purity of cathode copper reaches 95 - 98% of the base substance. It has also been found that stripping solutions progressively accumulates an insoluble precipitate comprising about 40% of lead, which may be attributed to the mechanical destruction of the active anode layer composed of lead oxides (PbO2). The study shows that it is necessary to look for a anode material to replace lead dioxide anodes having poor stability in this process.